Anaerobic co-digestion of swine manure with sweet potato or cassava in different c/n ratios - Villa, Lisandra Maraia; Orrico, Ana Carolina Amorim; Akamine, Luana Alves [UNESP]; Junior, Jorge de Lucas [UNESP]; Sunada, Natália da Silva (FapUNIFESP (SciELO), 2020)
Anaerobic co-digestion (AcoD) of waste is a method of increasing methane (CH4 ) yield and improving biofertilizer quality. This study aimed to evaluate the best AcoD conditions for swine manure (SM) with sweet potato (SP) or cassava (C) in different amounts in semi-continuous biodigesters. Initially, using batch biodigesters, an AcoD test of the SM with SP or C was performed, adopting carbon/nitrogen (C/N) ratios of 10/1, 13/1, 17/1, and 22/1. Based on the results, a C/N ratio of 10/1 was chosen, which was the proportion that resulted in the highest reduction of volatile solids (VS) and specific biogas production. From these results, the experiment was carried out in semi-continuous biodigesters, consisting of three treatments (control (SM), SP 10/1, and C 10/1) with five replicates and a hydraulic retention time (HRT) of 30 days. Total solid (TS) and volatile solid (VS) reductions, biogas and CH4 yields, alkalinity, and volatile acidity were measured. The control treatment differed from the others and resulted in decreased biogas yield (752 LN.kgVSadded-1), CH4 (449 LN.kgVSadded-1 ), and CH4 content (59.7%). The AcoD treatments (SP and C) did not differ significantly for biogas yield (respectively, 901 and 883 LN.kgVSadded-1) and CH4 (respectively, 590 and 547 LN.kgVSadded-1); however, they differed in CH4 content (65.5% and 61.9% respectively). The treatments showed general reduction averages of 76.1% and 85.9% for TS and VS, respectively, with no statistical difference found between them. The AcoD of the SM with SP or C increased the production and quality of the biogas, increasing the concentration of CH4 therein.
Co-digestão anaeróbia dos dejetos de suínos com batata doce ou mandioca em diferentes relações c/n
Keywords: Acidification; Anaerobic biodigestion; Carbohydrates; Methanogenesis; Tuberous roots